12-(4-Methoxyphenyl)-10-phenyl-3,4,5,6,8,10-hexaazatricyclo[7.3.0.0(2, 6)]dodeca-1(9),2,4,7,11-pentaene - Jotani, M.M.; Shah, R.D.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
In the title compound, C19H14N6O, the fused 12-membered tetrazolo/pyrimidine/pyrrole ring system is almost planar (r.m.s. deviation = 0.013 angstrom). The 4-methoxyphenyl and phenyl substituents on the pyrrole ring are both twisted with respect to the fused-ring system [dihedral angles = 25.39 (18) and 36.42 (18)degrees, respectively]. Intramolecular C-H center dot center dot center dot N interactions occur. In the crystal, molecules pack into layers in the ac plane and these are connected along the b axis via C-H center dot center dot center dot pi and pi-pi [centroid-centroid separation = 3.608 (3) angstrom] interactions.